2018
DOI: 10.1016/j.rmed.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of once-daily fluticasone furoate/vilanterol (FF/VI) versus twice-daily inhaled corticosteroids/long-acting β2-agonists (ICS/LABA) in patients with uncontrolled asthma: An open-label, randomized, controlled trial

Abstract: These findings suggest that, in a tightly controlled randomized controlled trial setting, once-daily FF/VI provides similar asthma control over 24 weeks to usual, twice-daily ICS/LABA in patients with asthma that is uncontrolled on ICS alone. FF/VI was well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Published data about indacaterol ( 4 ) and olodaterol ( 5 ) only provide the evidence that they maintain effective relaxation for over 24 h in asthma, and there is no specific dose and dose frequency for olodaterol ( 5 ) or its combination with ICS . Recent studies have shown that the new combination mometasone furoate/indacaterol acetate, also known as QMF149, may be a potential therapeutic option for asthma. , In addition, the efficacy of fluticasone furoate/vilanterol ( 6 ) in asthma has also being evaluated. , The once-daily dosing regimen associated with the use of these agents is an advantage over the traditional ICS/LABA combination therapy as adherence is enhanced.…”
Section: β2-agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Published data about indacaterol ( 4 ) and olodaterol ( 5 ) only provide the evidence that they maintain effective relaxation for over 24 h in asthma, and there is no specific dose and dose frequency for olodaterol ( 5 ) or its combination with ICS . Recent studies have shown that the new combination mometasone furoate/indacaterol acetate, also known as QMF149, may be a potential therapeutic option for asthma. , In addition, the efficacy of fluticasone furoate/vilanterol ( 6 ) in asthma has also being evaluated. , The once-daily dosing regimen associated with the use of these agents is an advantage over the traditional ICS/LABA combination therapy as adherence is enhanced.…”
Section: β2-agonistsmentioning
confidence: 99%
“…234,235 In addition, the efficacy of fluticasone furoate/ vilanterol (6) in asthma has also being evaluated. 236,237 The once-daily dosing regimen associated with the use of these agents is an advantage over the traditional ICS/LABA combination therapy as adherence is enhanced.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…12 Safety results of dual combination therapy with FF/VI have also shown a favorable risk profile, with headache, nervous system disorders, and nasopharyngitis reported as the most frequently occurring on-treatment AEs. 4,13 Treatment with umeclidinium (UMEC), a LAMA, was also not associated with significant safety concerns; the most frequently reported on-treatment AEs included headache, nasopharyngitis, abnormal product taste, and pharyngitis. 14,15 Single-inhaler triple therapy with the combination of FF/UMEC/VI is widely approved as a once-daily treatment for chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 99%
“…These randomized control studies have compared the effects of FF/VI DPI combination versus placebo or fluticasone propionate/salmeterol (FP/SLM) DPI on acute exacerbations, pulmonary function, health-related quality of life, and adverse effects, in patients with chronic asthma. In addition, there have been some reports to compare FF/VI DPI therapy with other ICS/LABA combinations, such as budesonide/formoterol (BUD/FM) DPI, and assess patient adherence in asthma inhaler treatment recently 15,16. Therefore, we conducted this randomized crossover study to compare the clinical effects and inhalation adherence barriers of once-daily FF/VI DPI versus twice-daily BUD/FM DPI in patients with controlled stable asthma on ICS/LABA treatment.…”
Section: Introductionmentioning
confidence: 99%